(untitled) (Encuentros, 2016)
The research paper describes the types of attachments in a group of young people with antisocial and psychopathic traits. The participants were 100 young Penal Responsibility System for Adolescents in Monteria, aged between 15 and 18 years (mean 16, 25, DT 2, 8). The study design was based on a descriptive quantitative approach. The measuring instrument were the Psychopathy Checklist: Youth Version. PCL: YV and scale Romantic and no romantic attachment. The results are consistent, as the theoretical basis revised where deprivation in the affective area since childhood may be an indicator influential in the development of a psychopathic or antisocial personality. Keywords: attachment style, young, antisocial traits, psychopathic traits and crime